The portrayals of women in advertisements and their brand-related impacts: A study in Vietnam - Nguyen, Chuong (2020)
The liberation movement in the 1960s seeking equal rights, opportunities and freedom for women initiated the interests in gender stereotypes in advertising. Since then, the pursuit of gender equality for women in different spheres of life has never stopped evolving. Nowadays, as advertising bombards our daily lives from the living rooms to every minute of our online interaction, this topic has also continuously received great attention from different disciplines such as marketing, advertising, media, sociology and women’s studies (Shao et al., 2014). The initial question for this topic is usually whether female stereotypes occur, to what degree, and on which variables. The cultural and timing variations of the topic create a need for new studies in different national contexts and points of time. While there has been an abundance of literature in the assessment of female stereotypes, the reasons behind such depictions have more room for further exploration because some major questions remain debatable. Two of them are the mirror and mold perspectives which hold contradictory beliefs about whether advertising reflects or influences gender roles in society (Furnham & Lay, 2019). Advertising effectiveness studies on female stereotypes are also quite popular, but brand-related effects, particularly from the practitioners’ perspective, have received very little attention. Therefore, this thesis investigates the female stereotypes in Vietnamese advertisements and their brand-related impacts from practitioners’ viewpoints. The study includes the quantitative content analysis of 228 Vietnamese TV and online advertisements and the qualitative content analysis of six in-depth interviews with market research professionals. The first phase assesses the phenomenon. The second phase provides deeper explanations for the first set of data and other brand-related implications. The triangulation of these two phases helps increase the overall reliability and validity for the study. The empirical findings indicated the female stereotypes in four aspects: age, location, background, and arguments. Nevertheless, there were only four out of ten measures demonstrated a clear tendency of stereotypes. This showed that while female stereotypes existed to a certain degree, they were not pervasive on every aspect of Vietnamese advertisements. A sign of movement towards more modern portrayals than three to ten years ago was also observed in the interviews. Women were typically stereotyped as being young, mostly at home rather than in a professional setting, and surrounded by children. When featuring in adverts which generated social rewards, females were most likely to offer the rewards while male received them. They mostly expressed opinions about a product rather than factual or concrete evidence. Although being classified as stereotypes, most of these images were considered as true reflectors of the current reality where women were still handling family caring roles and housework. This finding supported the mirror perspective that advertising reflects society. The interviews also revealed five brand-related impacts and implications concerning female roles portrayals. Firstly, the traditional or modern women depictions could both generate positive and negative impact. Secondly, knowing and understanding target consumers would help brands to resonate with them by communicating relevant content. Thirdly, in both traditional or progressive messages, it was critical to maintain a good balance within the social and cultural norms. Fourthly, digital channels would be a potential media platform for more progressive messages. Finally, social progress, brand positioning, and stakeholders’ vision were the three key areas to focus for practitioners when considering the appropriate women portrayals for their advertisements.